PELATIHAN PEMBUATAN VCO (VIRGIN COCONUT OIL) DALAM MEWUJUDKAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) PADA SISWA KELAS VII SMP WARDHANI - Isrianto, Pramita Laksitarahmi; Wilujeng, Sukian; Marmi, Marmi; Sunaryo, Sunaryo; Ramadhanty, Erlinda Shella; Setianingsih, Indri (Jurnal Terapan Abdimas, 2024)
Abstract. The development of creativity in students in adolescence needs to be improved because in adolescence the curiosity for something new is higher. Therefore, it is necessary to hone their talents and creativity with positive things. As for the purpose of carrying out community service to students in order to develop knowledge of local wisdom products and skills that are still minimal, the idea of positive student creativity makes school conditions require a thought of transformation of science and technology by utilizing existing potential, so that it can shape the character of the community, especially students and students to be self-sufficient without leaving formal education at school. The creative solution that can be provided is to provide knowledge and training related to VCO (Virgin Coconut Oil) to seventh grade students of Wardhani Junior High School. VCO (Virgin Coconut Oil) is a pure coconut oil that is very beneficial for health. The method of implementation is providing material on the understanding and benefits of VCO, and demonstrating manufacturing techniques with the stages of preparation, implementation, assistance and evaluation. The results of the activity obtained 90% of participants have understood the basic techniques of making VCO and later students can have skills in developing VCO products into business opportunities to become entrepreneurs at a young age. Abstrak. Pengembangan kreativitas pada siswa-siswi pada usia remaja perlu ditingkatkan karena pada usia remaja rasa ingin tahu akan sesuatu yang baru lebih tinggi. Oleh sebab itu perlu mengasah bakat dan kreativitasnya dengan hal yang positif. Adapaun tujuan dilaksanakan pengabdian pada siswa siswi agar mengembangkan pengetahuan produk kearifan lokal dan keterampilan yang masih minim ide kreativitas siswa yang bersifat positif membuat kondisi sekolah membutuhkan suatu pemikiran transformasi ilmu pengetahuan dan teknologi dengan memanfaatkan potensi yang ada, sehingga dapat membentuk karakter masyarakat khususnya siswa dan siswi untuk berdikari tanpa meninggalkan pendidikan formal di sekolah. Adapun solusi kreatif yang dapat diberikan yaitu memberikan pengetahuan dan  pelatihan terkait  VCO (Virgin Coconut Oil) pada siswa kelas VII SMP Wardhani. VCO (Virgin Coconut Oil)  merupakan minyak kelapa murni  yang sangat bermanfaat bagi kesehatan. Metode  pelaksanaannya yaitu pemberian materi tentang  pengertian dan manfaat VCO, dan  demonstrasi teknik pembuatan dengan tahapan persiapan, pelaksanaan, pendampingan dan evaluasi. Hasil dari kegiatan diperoleh 90% peserta sudah memahami teknik dasar pembuatan VCO dan nantinya siswa-siswa  dapat memiliki keterampilan  dalam mengembangankan Produk VCO menjadi peluang usaha menjadi enterpreuner  pada usia remaja.